Deviazione. Per un approccio a “Dante e Fortini” - Vegliante, Jean-Charles (L’ospite ingrato, 2021)
After a brief investigation into the available corpus, the essay proposes to shift the focus from textual (metrical, stylistic) convergences to Fortini’s more general conception of translation, applying it to a personal and recent “remake” of the beginning of the Comedy.